Edukasi Tentang Pola Makan Sehat Untuk Mengurangi Resiko Dismenore Pada Remaja - Oni Dwi Yanti; Ema Wahyu Ningrum; Maya Safitri (Yayasan Inspirasi El Burhani, 2026)
Introduction: Adolescence is a transitional phase characterized by physical, psychological, and reproductive system changes, including menstruation. Dysmenorrhea is a common problem among adolescent girls that can interfere with daily activities and is influenced by unhealthy dietary habits, while adolescents’ understanding of the relationship between diet and reproductive health remains limited. Objective: The purpose of this community service activity was to improve adolescents’ knowledge and encourage the adoption of healthy eating patterns to reduce the risk of dysmenorrhea. Method: This activity was conducted through health education using interactive lectures, discussions, educational videos, and booklet distribution. Evaluation was carried out using pre-test and post-test, as well as dietary monitoring using the Food Frequency Questionnaire (FFQ) for two weeks after the intervention. Result: The activity involved 21 female students and showed a significant improvement in knowledge. The proportion of students with good knowledge increased from 47.37% to 73.68%, while the moderate category decreased from 36.84% to 21.05% and the poor category decreased from 15.79% to 5.26%. The average knowledge score also increased. Conclusion: Health education on healthy eating patterns is effective in improving knowledge and encouraging behavioral changes among adolescents. Continuous school-based interventions are needed to support reproductive health and reduce the impact of dysmenorrhea.